PENGARUH DUKUNGAN SOSIAL TERHADAP PENYESUAIAN DIRI MASA PENSIUN DESA FODO KECAMATAN GUNUNG SITOLI SELATAN KOTA GUNUNG SITOLI - Sri Ramadhani; Laksana Tobing; Indo Mora; Lidia Realitas (Psikologi Universitas Sari Mutiara Indonesia, 2021)
Entering retirement, the individual will experience an important change in the development of his life, which is marked by social changes. Changes caused by this retirement period require adjustment. Someone who is facing retirement needs social support in facing retirement. This quantitative study aims to determine the effect of social support on retirement adjustment in Fodo Village, South Gunungsitoli District, Gunungsitoli City with 34 samples taken in this study. Based on the results of data analysis, it can be concluded that there is a significant effect between social support on self-adjustment with a correlation coefficient (R) of 54.3% which means that there is a fairly close relationship between social support and retirement adjustment and the coefficient of determination (R square) indicates that adjustment self-retirement is influenced by social support by 29.5%.